2011
DOI: 10.1103/physrevlett.107.266801
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Signatures of the Intrinsic Spin Hall Effect in Closed Systems

Abstract: We study a two-dimensional electron system in the presence of spin-orbit interaction. It is shown analytically that the spin-orbit interaction acts as a transversal effective electric field, whose orientation depends on the sign of the z-axis spin projection. This effect does not require any driving electrical field and is inherent to the spin-orbit interactions present in semiconductor materials. Therefore, it should manifest in both closed and open systems. An experiment is proposed to observe the intrinsic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that, in the generic k-linear system, the effective coupling between spin z component s z and orbital angular momentum L z is given by (−2m/ 4 )det( β)s z L z [26,27]. When det( β) = 0, the effective coupling between spin and orbital angular momentums in the z component vanishes; thus, both conventional and spin torque currents must be zero.…”
Section: Berry Phase Inmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that, in the generic k-linear system, the effective coupling between spin z component s z and orbital angular momentum L z is given by (−2m/ 4 )det( β)s z L z [26,27]. When det( β) = 0, the effective coupling between spin and orbital angular momentums in the z component vanishes; thus, both conventional and spin torque currents must be zero.…”
Section: Berry Phase Inmentioning
confidence: 99%
“…The physical meaning of the topological number det( β)/|det( β)| = ±1 is as follows. It has been shown that det( β) governs the effective coupling 2 of s z and L z via det( β)s z L z [26,27] and, thus, represents the orbital chirality of the spin s z . When det( β)/|det( β)| changes from +1 to −1, the current carrying +s z changes orbital chirality from L z to −L z , and −s z changes orbital chirality from −L z to +L z .…”
Section: Berry Phase Inmentioning
confidence: 99%
See 1 more Smart Citation
“…We neglect effects of order α 2 R such as interfaceinduced magnetic anisotropy, contributions to Gilbert damping [25,26], and to the nonadiabaticity parameter [27]. We introduce the unitary transformation [28,29]…”
mentioning
confidence: 99%